Posterior reversible encephalopathy syndrome in systemic lupus erythematosus: Pooled analysis of the literature reviews and report of six new cases - Shaharir S.S.; Remli R.; Marwan A.A.; Said M.S.M.; Kong N.C.T. (2024)
Introduction: Posterior reversible encephalopathy syndrome (PRES) is a rare neurological disorder which is increasingly recognized to occur in systemic lupus erythematosus (SLE). Objective: The purpose of this study was to identify the characteristics of SLE patients with PRES and the associated factors of the poor outcome among them. Methods: We investigated SLE patients who developed PRES between 2005-2011 at the Universiti Kebangsaan Malaysia Medical Centre. A comprehensive literature search was done to find all published cases of PRES in SLE. Pooled analysis was conducted to identify the factors associated with poor outcome. Results: There were 103 cases of PRES in SLE published in the literature but only 87 cases were included in the analysis in view of incomplete individual data in the remaining cases. The majority of the cases were Asians (74.2%), female (95.4%) with mean age of 26.3±8.8 years. PRES was highly associated with active disease (97.5%), hypertension (91.7%) and renal involvement (85.1%). We found that 79 patients had a full recovery (90.8%) with a mean onset of full clinical recovery in 5.6±4.1 days. On univariate analysis and logistic regression analysis the predictors of poor outcome, defined as incomplete clinical recovery or death, were intracranial hemorrhage, odds ratio (OR) 14 (1.1-187.2), p=0.04 and brainstem involvement in PRES, OR 10.9 (1.3-90.6), p=0.003. Conclusion: Intracranial hemorrhage and brainstem involvement were the two important predictors of poor outcome of PRES. Larger prospective studies are needed to further delineate the risk of poor outcome among them.